Purchase Intention di Era TikTok : Peran Trust dalam Pengaruh Online Customer Review dan Social Media Influencer Terhadap Produk Sunscreen The Originote Pada Gen Z di Surabaya - Clarissa Aurora Putri, Brilivena; Dermawan , Rizky; Mukti Azhar, Ratih (Jurnal Riset Pendidikan Ekonomi, 2025)
The research shows to examine the influence of Online Customer Reviews and Social Media Influencers on Purchase Intention for The Originote sunscreen products, with Trust as a mediator among Gen Z TikTok users in Surabaya. This research uses a quantitative approach involving 96 respondents through purposive sampling and is analyzed using PLS-SEM. The study reveals that Online Customer Reviews and Social Media Influencers generate a favorable and significant effect on Purchase Intention, and Trust mediates both relationships. These findings indicate that Gen Z actively uses digital marketing as an information source, where trust in honest and non-manipulative reviews is a crucial factor in shaping purchase intentions. This study is limited by its geographic scope and the lack of detailed exploration of influencer characteristics. For Gen Z consumers, it is recommended to be more selective when evaluating reviews and content on TikTok. Meanwhile, companies are advised to build a positive image on TikTok to foster audience trust. Future researchers are encouraged to explore variables such as cognitive behavior in the context of digital consumer behavior.